2017
DOI: 10.1039/c7nr04352j
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatible and blood–brain barrier permeable carbon dots for inhibition of Aβ fibrillation and toxicity, and BACE1 activity

Abstract: Amyloid-β peptide (Aβ) fibrillation is pathologically associated with alzheimer’s disease (AD), and this has resulted in the development of an Aβ inhibitor which is essential for the treatment of AD. However, the design of potent agents which can target upstream secretases, inhibit Aβ toxicity and aggregation, as well as cross the blood-brain barrier remains challenging. In, this research carbon dots for AD treatment were investigated in vitro using experimental and computational methods for the first time. th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(42 citation statements)
references
References 31 publications
(35 reference statements)
0
42
0
Order By: Relevance
“…[20] Leblanc et al also reported that GQDs can inhibit Aβ fibrillation, suppress BACE1 activity and delay the formation of Aβ42 toxic species in vitro by using the hydrophilic surface. [21] In addition, the large available surface of graphene oxide and their proteincovered surfaces were confirmed to be able to delay the Aβ fibrillation process via adsorption of amyloid monomers. [22] However, no quantitative explanation was available till now.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…[20] Leblanc et al also reported that GQDs can inhibit Aβ fibrillation, suppress BACE1 activity and delay the formation of Aβ42 toxic species in vitro by using the hydrophilic surface. [21] In addition, the large available surface of graphene oxide and their proteincovered surfaces were confirmed to be able to delay the Aβ fibrillation process via adsorption of amyloid monomers. [22] However, no quantitative explanation was available till now.…”
Section: Resultsmentioning
confidence: 96%
“…(a) 10 μM Aβ42 incubated with 0, 2, 5 and 10 μg/ml graphene quantum dots. Data adopted from; (b) 550 μM Aβ33‐42 incubated with 0, 5, 20 and 80 μg/ml graphene oxide. Data adopted from .…”
Section: Resultsmentioning
confidence: 99%
“…Motivated by the ability of NPs to cross the blood-brain-barrier, much effort has been devoted to understand the effect of nanoparticles on protein aggregation in the context of neurodegenerative diseases such as that of amyloid-beta peptide in Alzheimer's disease. CQDs [240][241][242][243] and GQDs 244,245 positively impacted this field as they showed to be effective inhibitors. CQDs of 6 nm in size, prepared from carbon powder by acid treatment at elevated temperature, were able to efficiently inhibit insulin fibrillation in a concentration-dependent manner.…”
Section: Inhibition Of Protein Aggregationmentioning
confidence: 99%
“…Using human transferrin modified CQDs and zebrafish as in vivo model, the ability of CQDs to cross the brain blood boundary (BBB) was evidenced. 243…”
Section: Inhibition Of Protein Aggregationmentioning
confidence: 99%
“…Among all the categories of nanoparticles, carbon-based nanomaterials have been attracting extraordinary interests in the development of amyloid nanoinhibitors due to their high biocompatibility and biodegradability, ease of synthesis and high feasibility for further functionalization. A variety of carbon nanoparticles, including graphene/graphene oxide, carbon nanotube (CNT), fullerene and C-dots [192][193][194][195][196][197], has been proved capable to modulate amyloid aggregation. Due to the ordered structure of CNT and fullerene, the interactions between amyloid peptides and these two types of carbon nanomaterials have been extensively investigated by in silico molecular dynamic (MD) studies.…”
Section: Nanoparticle Based Inhibitorsmentioning
confidence: 99%